PENGARUH STORE ATMOSPHERE, VARIASI PRODUK, E-WOM TERHADAP KEPUTUSAN PEMBELIAN PRODUK FOOD COURT KOTA MADIUN - Indra Ayu Fatmala; Fransisco Aldi Bahari (UNIVERSITAS PGRI MADIUN, 2024)
This study aims to determine the effect of store atmosphere, product variety, and electronic word of mouth (E-WOM) on purchasing decisions for food court products in Madiun city. This study uses a quantitative research method. The population of this research is Consumers Food Court in Madiun city as many as 384 people through a questionnaire. The data collection technique for this research used a purposive sampling technique. The research data analysis method uses Multiple Linear Regression analysis using the SPSS program. Data analysis was performed using the Classical Assumption Test, Multiple Linear Test, t test. The results of this study prove that 1) Store Atmosphere has a significant effect on the Purchase Decision of Food Court products in Madiun City. 2) Product Variation has no effect on the Purchase Decision of Food Court products in Madiun City. 3) Electronic Word Of Mouth has a significant effect on the Purchase Decision of Food Court products in Madiun City.